2016
DOI: 10.1097/md.0000000000005461
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a long-acting anticoagulant rodenticide poisoning cohort with vitamin K1 during the maintenance period

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…[ 21 24 ] A study of 56 patients with anticoagulant rodenticides poisoning showed that there was not a significant dose–effect relationship between the concentration of rodenticides and the requirement of vitamin K1 during the maintenance period. [ 10 ] For severe cases, transfusion of fresh frozen plasma, prothrombin complex, and/or recombinant coagulation factor VIIa should be given. Muscle injection of acetamide is the targeted treatment for fluoroacetamide, [ 16 ] and calcium therapy can ameliorate cardiac arrhythmias induced by fluoroacetamide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 21 24 ] A study of 56 patients with anticoagulant rodenticides poisoning showed that there was not a significant dose–effect relationship between the concentration of rodenticides and the requirement of vitamin K1 during the maintenance period. [ 10 ] For severe cases, transfusion of fresh frozen plasma, prothrombin complex, and/or recombinant coagulation factor VIIa should be given. Muscle injection of acetamide is the targeted treatment for fluoroacetamide, [ 16 ] and calcium therapy can ameliorate cardiac arrhythmias induced by fluoroacetamide.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 , 9 ] Interfering with blood coagulation, bromadiolone induces varying degrees of hemorrhage, such as ecchymoses, gingival bleeding, epistaxis, gastrointestinal bleeding, hematuria, vaginal bleeding, and rarely SAH. [ 6 , 10 14 ] Besides coagulopathy, patients with bromadiolone poisoning sometimes present with headache, seizure, hallucinations, dizziness, consciousness impairment and a few other symptoms of central nervous system (CNS). [ 7 ] Fluoroacetamide poisoning often causes damages in heart (QT prolongation, arrhythmia, myocardial damage), digestive system (vomiting, nausea, burning sensation in the epigastrium), and CNS (seizure, aphasia, myasthenia, and coma).…”
Section: Introductionmentioning
confidence: 99%
“…Rice is usually washed with water before cooking, and the concentration of leftover bromadiolone in a rice meal might be less than 0.005%. Bromadiolone is thermally stable below 200 degrees Celsius [ 7 ]. In cases without washing, a bowl of rice is calculated to contain 9 mg of rat poison.…”
Section: Discussionmentioning
confidence: 99%
“…These findings seemed to not be applicable in these cases of low-dose and repeated LAAR exposure. The patients who suffered from significant bleeding and abnormal INR values required the use of vitamin K1 therapy even with serum bromadiolone level less than 4 ng/mL [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many clinicians have experience with the treatment of supratherapeutic INRs; however, LAAR poisoning requires high-dose and long-term vitamin K treatment, as the half-life of LAAR is between 10 and 70 days, which is 10–50 times longer than the half-life of warfarin 2. For patients with active bleeding, the first-line haemostatic therapy is FFP and haemostatic dosing of vitamin K 1 (phytonadione) 8. Vitamin K 1 dosing is titrated to response based on monitoring coagulation assay values (PT/INR) and refractory bleeding, with the median duration of vitamin K 1 treatment reported as 140 days.…”
Section: Discussionmentioning
confidence: 99%